(Dynamic) Kinetic Resolution of Enamines/Imines: Enantioselective N‐Heterocyclic Carbene Catalyzed [3+3] Annulation of Bromoenals and Enamines/Imines - Chen, Kun‐Quan; Gao, Zhong‐Hua; Ye, Song (Angewandte Chemie International Edition, 2019)
The enantioselective N‐heterocyclic carbene catalyzed [3+3] annulation of α‐bromoenals by dynamic kinetic resolution (DKR) of enamines and normal resolution of α,α‐disubstituted imines were developed. The corresponding substituted dihydropyridones were isolated in good yields with excellent diastereo‐ and enantioselectivities, and a high selective factor (up to 83) was realized for the resolution of α,α‐disubstituted imines. The S factor: The enantioselective N‐heterocyclic carbene (NHC) catalyzed [3+3] annulation of α‐bromoenals by dynamic kinetic resolution (DKR) of enamines, and normal resolution of α,α‐disubstituted imines were developed. The corresponding substituted dihydropyridones were isolated in good yields with excellent diastereo‐ and enantioselectivities, and a high selectivity factor was realized for the resolution of α,α‐disubstituted imines.